2015
DOI: 10.3109/02713683.2015.1062114
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Decellularization: A Method of Recycling Unsuitable Donor Tissue for Clinical Translation?

Abstract: Background: There is a clinical need for biomimetic corneas that are as effective, preferably superior, to cadaveric donor tissue. Decellularized tissues are advantageous compared to synthetic or semi-synthetic engineered tissues in that the native matrix ultrastructure and intrinsic biological cues including growth factors, cytokines and glycosaminoglycans may be retained. However, there is currently no reliable, standardized human corneal decellularization protocol. Methods: Corneal eye-bank tissue unsuitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
117
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(126 citation statements)
references
References 59 publications
5
117
0
4
Order By: Relevance
“…Additionally, this highlights a common problem: While thin tissues can be easily decellularized, central regions of thicker tissues are hardly reached by DC agents . In our experiments DAPI and H.E.…”
Section: Discussionmentioning
confidence: 68%
“…Additionally, this highlights a common problem: While thin tissues can be easily decellularized, central regions of thicker tissues are hardly reached by DC agents . In our experiments DAPI and H.E.…”
Section: Discussionmentioning
confidence: 68%
“…Studies have shown that SDS and TX‐100 have a great ability to remove GAG of tissue. Therefore, researchers are trying to save GAG as much as possible in the matrix during the decellularization process . In this study, it has been revealed that there was a significant difference in GAG content of the untreated group compared to that of the treated groups.…”
Section: Discussionmentioning
confidence: 95%
“…These studies suggest that TX alone is not a strong enough detergent to sufficiently decellularize corneas. On the other hand, since TX is not able to break protein‐to‐protein interactions, disruption of the histo‐architecture is not as complete as with SDS, and there remain reduced transparency and edema after use of TX …”
Section: Decellularization Methodsmentioning
confidence: 99%
“…Hypertonic saline has been used to decellularize human, porcine, rabbit, and ostrich corneas . HS is an effective decellularization agent due to its ability to disrupt DNA‐to‐protein interactions and to induce osmotic lysis .…”
Section: Decellularization Methodsmentioning
confidence: 99%